NEMIS TILINI O‘QITISH METODLARI VA ULARNING AHAMIYATI (Лучшие интеллектуальные исследования, 2025)
Annotation: this article provides information on methods of teaching the German language and their importance.Keywords: foreign language, phonetic, lexical, grammatical features, multilingualism (polyglot), synonymy criterion, linguistic (indifferent) or narrow, speech.Annotatsiya: Ushbu maqolada nemis tilini o‘qitish metodlari va ularning ahamiyati haqida ma’lumotlar keltirilgan.